Retraction Note: Cardiac structural remodeling in hypertensive cardiomyopathy. Issue 12 (December 2018) - Sun, Si-jia; Yao, Jia-lu; Xu, Lang-biao; Rui, Qing; Zhang, Nan-nan; Chen, Min; Jiang, Yu-feng; Yang, Hua-jia; Zhou, Ya-feng
The authors are retracting this article [1]. In their recent work the authors have found that the degree of fibrosis in the different walls of the left atrium in pigs with hypertensive cardiomyopathy is the same. Sirius Red staining (another method to test for fibrosis) showed that there was no difference between the different walls. The authors are unable to explain this inconsistency. All authors agree with this retraction.